Swallowing - Physiology, Disorders, Diagnosis and Therapy - Mankekar, Gauri (Springer India : Imprint: Springer, 2015)
Swallowing difficulty or dysphagia is a common disorder and affects all age groups from the newborn to the elderly. Several medical conditions like lack of dentition, gastroesophageal reflux disease, eosinophilic esophagitis, cardiomegaly and strokes can cause dysphagia. It can also follow head -neck surgeries. It is important to diagnose and treat dysphagia, otherwise it can lead to malnutrition and dehydration. Improved understanding of the physiology of swallowing, advances in endoscopic and radiological techniques along with an increasing elderly population has resulted in development of a separate swallowing disorders discipline. This book would be an aid for clinicians, educators and trainees from the fields of speech language pathology, pediatrics, otolaryngology, gastroenterology, oncology, neurology, geriatrics and rehabilitation, all of who form a part of the multidisciplinary swallowing team.